Нові трансплантати для пластики передньої схрещеної зв’язки за методом "all-inside" - Головаха, Максим Леонідович; Орлянський, В.; Бенедетто, К. П.; Golovakha, M. L.; Orljanskі, V.; Benedetto, K. P. (My University, 2019)
Improving the technique of anterior cruciate ligament (ACL) reconstruction is developing in the following areas: reduction of surgical trauma, improvement of the anatomical position of the graft, increased strength of its attachment, stimulation of regeneration of attachment sites, modification of postoperative of rehabilitation treatment. The «all-inside» technique meets most requirements. The recovery period of the patient after ACL reconstruction significantly associated with the speed of integration of the transplant into the surrounding tissue. Objective: to develop a method for using transplants from the patellar ligament (BTB) and quadriceps tendon (QT) during ACL reconstruction according to the «all-inside» technique. Methods: the study included patients (12 men, 2 women) who in addition to ACL reconstruction had meniscus removal, meniscus suture, cartilage shaving and microfracturing of small defects (no more than 3 cm2). Revision operations was carried out in 3 patients. The channels were drilled with a RetroDrill® t ool o r F lipCutter ®. The grafts in the femur and tibia were fixed using TightRope ® suspension system or its analogue. Results: a method was developed for the use of BTB and QT grafts with 180° turnover of bone fragment to restore ACL according to the method «allinside ». Clinical testing of the method in primary and the revision of the ACL reconstruction has shown good and excellent results. On 2–3 days, VAS pain indicator is 3–4 points, after a week all patients recovered knee flexion up to 90°. Instability of the knee joint is not detected. After 12 months 71.2 % of patients were assigned to group A on the IKDC scale. Conclusions: proposed method can be used in the primary and, especially, revision ACL reconstruction, because by turning the bone fragment you can get the end of the graft significantly larger diameter comparing with traditional methods for the preparation of BTB and QT transplants. Незважаючи на створення нових технологій, питома вага незадовільних результатів відновлення передньої схрещеної зв’язки (ПСЗ) не має тенденції до зниження. За даними різних авторів, рецидиви, пов’язані з ушкодженням трансплантата ПСЗ досягають 5–14 %. Повернення пацієнта на колишній рівень фізичної активності після операції ще менше — від 54 до 86 % [1–4]. Причини ушкоджень трансплантата наводять найрізноманітніші. Найчастіше мова йде про порушення його позиції, причиною якого є неправильне розміщення каналів у стегновій і рідко коли у великогомілковій кістці. Триває дискусія щодо вибору трансплантата для пластики ПСЗ [4–7]. Важливий фактор — недостатньо великий діаметр трансплантата. Опубліковано інформацію про слабку його фіксацію через неправильне застосування або внаслідок запалення в місці контакту з кісткою. Неможна не згадати про необхідність ураховувати будову ПСЗ із огляду на двопучкову концепцію, ігнорування якої також обумовлює певну частку невдач.
New grafts for anterior cruciate ligament grafting using the «all-inside» method
Keywords: knee; arthroscopy; anterior cruciate ligament; колінний суглоб; артроскопія; передня схрещена зв’язка